Risk Management and Organizational Resilience: Analysis of the Italian Scenario During Covid-19 Pandemic, with A Look at the Challenges of Technology and Sustainability - Cristina, Renzetti; Lucio, Mango (Journal of Big Data Research, 2020)
The Coronavirus emergency represents an epochal challenge for all world health organizations. In these times of profound destabilization of healthcare organizations, become urgent some thoughts on how to deal with the organization and re-engineering process as well as on concepts, relatively new, such as "resilience" and "business continuity". The company management need having to predict, design and plan a profound process of change in their Clinical and Corporate Governance. With the implementation of phases 2 and 3 of management of the pandemic and the coexistence of doctors and citizens with the new Coronavirus, it has become a priority to develop territorial models of assistance to established or suspected Covid patients, starting with the creation of monitoring networks based on the model of the “sentinel” general practitioner. One of the main concerns of Healthcare, since the beginning of the Covid-19 emergency has been to get closer to the citizen-patient. It is therefore necessary to find stimuli to restart with new methods of care, new health and social-health services, moving the current care paradigm for Covid-19 from the hospital to the territory, optimizing the constituent elements of the districts, primary care and general practice in a multidisciplinary approach.
Keywords: Covid-19; Risk Management; Resilience; General practice